On the 3-D reconstruction of Coronal Mass Ejections using coronagraph data - MC ATEER, ROBERT THOMAS JAMES; GALLAGHER, PETER THOMAS (Copernicus Publications, 2010)
Coronal Mass ejections (CMEs) are enormous eruptions of magnetized plasma expelled from the Sun into the interplanetary space, over the course of hours to days. They can create major disturbances in the interplanetary medium and trigger severe magnetic storms when they collide with the Earth's magnetosphere. It is important to know their real speed, propagation direction and 3-D configuration in order to accurately predict their arrival time at the Earth. Using data from the SECCHI coronagraphs onboard the STEREO mission, which was launched in October 2006, we can infer the propagation direction and the 3-D structure of such events. In this review, we first describe different techniques that were used to model the 3-D configuration of CMEs in the coronagraph field of view (up to 15 R?). Then, we apply these techniques to different CMEs observed by various coronagraphs. A comparison of results obtained from the application of different reconstruction algorithms is presented and discussed.
PUBLISHED
Keywords: Astrophysics; Coronal Mass ejections (CMEs)